Answer:
4:7
Step-by-step explanation:
4 grape candies : 7 total candies (grape + cherry)
1) y-intercept => x = 0, => y = f(0) = 0 - 0 + 0 - 36 = -36
2) x-intercept => y = 0 => factor the function (start by dividing by x -2)
f(x) = (x-2)(x-3)(x-6) =0 => x =2, x = 3, x = 6 (these are the x-intercepts)
3) critical points:
between x = 2 and x = 3, there is a local maximum
between x =3 and x = 6 there is a local minimum
3) Shape.
The function comes growing from - infinity.
In the third quadrant the function is negative (it does not pass throuhg the second quadrant)
It enters to the fourth quadrant intercepting the y-axis at y = -36. It continues growing and intercepts the x-axis at x = 2.
It continues increasing until a maximum local positive value, starts to decrease, intercepts the x-axis at x = 3, continues decreasing, becomes negative, gets a local minimum in the fourth quadrant, starts to increase, intercepts the x-axis at x = 6, becomes positive, and continues growing.
A function f(x) has solutions if we can find a value to plug in that leads to 0. In other words, there are solutions to f(x) = 0. Another term for "solution" is "root" or "x intercept"
An exponential function may cross the x axis at one point only. Though there are plenty of cases when there are no solutions at all. For instance, in the case of f(x) = (2^x) + 10
The right hand side will never be equal to zero no matter what you plug in for x. The graph will never cross the axis.
To answer your question, yes it is possible to have an exponential equation to have no solutions.
Answer: 12, 15, 11, 28
Explanation:
14. FC is half of AC so the length of FC is 12.
15. BD is 30 and half of that is BC or 15. AB and BC have same length so it is also 15.
16. ED and BE have same length so it is also 11.
17. BD is twice of AB so if AB is 14, BD will be 28.
Would appreciate a brainly <3
f(x)= -2x-3
Step-by-step explanation:
Step 1:
Let the sequence given here is -5, -7, -9, -11, -13 ......
Here the first term (a₁) of sequence is -5
And the common difference between the numbers in the sequence is
d= (-7-(-5)) = -7+5 = -2
Let the number of terms be x
Step 2;
To find the sequence function basic arithmetic sequence formula is
aₙ = a₁ + d( x-1)
Applying the values we get
f(X) = -5 + ((-2)(X-1))
on simplification
f(X) = -5 + (-2X+2)
f(X)= -5+2-2X
f(X)= -3-2X